Malpraktek dalam Tinjauan Hukum Islam - Sanusi, Ahmad (Al-Manahij: Jurnal Kajian Hukum Islam, 2007)
Mallpractice is a medical treatment that includes doing something forbidden in caring patients or did not doing the thing that bad to be done or neglecting the duty by did not diagnose property and gave a standardized medicine. Islamic law gives diyat as a sanction for those who did a malpractice.